SUBSTRATE TEMPERATURE DEPENDENT OPTICAL AND STRUCTURAL PROPERTIES OF VACUUM EVAPORATED CdTe THIN FILMS - Mandal, Mousumi; Choudhury, Shamima; Das, Chitra; Begum, Tahmina (European Scientific Journal, ESJ, 2014)
Substrate temperature dependent optical and structural properties of Cadmium Telluride (CdTe) thin films were studied. Films were grown onto glass substrate by thermal evaporation method in high vacuum (10-6 Torr) with varying thickness (200 500 nm). All the films were characterized optically by UV-VIS-NIR spectrophotometer in photon wavelength range (300 nm 2500 nm). The optical transmittance and reflectance were utilized to compute the absorption coefficient, refractive index and band gap energy of the films. The calculated band gap energy was found to increase (1.49eV 1.55eV) with varying thickness and to decrease (1.56eV 1.46eV) with varying substrate temperature. The X-ray diffraction (XRD) patterns exhibited the zinc-blende structure of CdTe films with (111) preferential orientation. The lattice parameters, grain size, average internal stress, micro strain, dislocation density in the films were calculated. The grain size was varied from 32nm to 52nm with variation of substrate temperature. Micro strain and dislocation density were also found to vary between 0.69×10-3 1.12×10-3 and 3.59×1010 cm-2 9.49×1010 cm-2 respectively.